Representasi Gaya Hidup Konsumtif Generasi Muda Pada Meme “Lambang Baru Kemapanan” - Azmi, Rayhan Muhammad; Astuti, Sri Wahyuning (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The young generation is considered to have and implement consumer lifestyle practices that have indirectly harmed them. This consumer life then received criticism for using memes as a medium. The research method used is Norman Fairclough's critical discourse analysis by implementing the 3 dimensions of critical discourse analysis and then analyzing it using Norman Fairclough's